Ecology of inshore notothenioid fish from the Danco Coast, Antarctic Peninsula - Casaux, Ricardo Jorge (2003)
A total of 1,103 inshore notothenioid fish were caught by means of trammel-nets in 4 sites surrounding Cierva Point (Moss Island 1; Moss Island 2; Sterneck Island; Leopardo Island), Danco Coast, West Antarctic Peninsula, during February and March 2000. The families Nototheniidae, Channichthyidae and Bathydraconidae were represented in the samples, Notothenia coriiceps being the dominant fish of the area. Gobionotothen gibberifrons and Trematomus newnesi followed in importance. In general, the fish sampled agreed in terms of number and mass with those of the South Shetland Islands area, except for a marked higher occurrence of G. gibberifrons in the Danco Coast. This supports the hypothesis that the commercial fishery around the South Shetland Islands at the end of the 1970s was responsible for the decrease in the inshore population of G. gibberifrons in that area during the last 17 years. Information on morphometry, reproduction and diet of the fish species caught is provided.